PENGENDALIAN PROYEK SISTEM INFORMASI DENGAN METODE CPM (CRITICAL PATH METHOD) - Suryati Suryati (UNIVERSITAS INDO GLOBAL MANDIRI)
To control a project we used CPM method which very use full to arrange a planning, scheduling and project control. Project is combined form many activity which link and it must followed by order before the entire work activity can be done successfully. To take on project controlling application is to find a critical dot to scheduling project. An arrow diagram is used to presenting an activity where the point ist to showed an a progress development way in project. The entire arrow diagram is giving a graphic representation aboat the relation between many project activity. In order way, circle diagram is used to presenting an even, where it doesn’t need time. On arrow hilt (where the activity begun) and on the end of arrow (where the activity end). The event first number are smaller than tic number. This CPM method is able to give a clear view about process certain critical line to make certain to a time schedule. Keyword : slack/float, crash, Jalur Kritis, dummy ,Slope.